Deputy in the Payment of Debt in the Legal System of Afghanistan - Mosavi, Sayed Abbas (Journal of Social Sciences - Kabul University, 2023)
In the civil law, the performance of dept is accepted as the most important way of the fall down the obligation. (Issue) Although in the discussion of performance, non-debtor's performance is also accepted, but according to the condition of the debtor's permission or the existence of a third party's interest in the payment, the paying third party does not have the authority to refer to the debtor in the absence of the above conditions. One of the solutions ways to solving those problems is being the third-party as a deputy. (Purpose) of this research is to examine it. (Method) In this research, by using the descriptive-analytical type of qualitative research method to collect data and review articles 903-907 of the Civil Code, we reach this conclusion (result) being deputy in third party payment with different forms but the same effect of transferring guarantees and supplies is accepted.